Sensitivities to charged-current nonstandard neutrino interactions at DUNE. (3rd November 2017) - Bakhti, Pouya; Khan, Amir N; Wang, W
Abstract: We investigate the effects of charged-current (CC) nonstandard neutrino interactions (NSIs) at the source and at the detector in the simulated data for the planned Deep Underground Neutrino Experiment (DUNE). We neglect the neutral-current NSIs at the propagation because several solutions have already been proposed for resolving the degeneracies posed by neutral-current NSIs but no solutions exist for the degeneracies due to the CC NSIs. We study the effects of CC NSIs on the simultaneous measurements of θ 23 and δ CP in DUNE. The analysis reveals that 3 σ C.L. measurement of the correct octant of θ 23 in the standard mixing scenario is spoiled if the CC NSIs are taken into account. Likewise, the CC NSIs can deteriorate the uncertainty of the δ CP measurement by a factor of two relative to that in the standard oscillation scenario. We also show that the source and the detector CC NSIs can induce a significant amount of fake CP-violation and the CP-conserving case can be excluded by more than 80% C.L. in the presence of fake CP-violation. We further find DUNE's potential for constraining the relevant CC NSI parameters from the single parameter fits for both neutrino and antineutrino appearance and disappearance channels at both the near and far detectors. The results show that there could be improvements in the current bounds by at least one order of magnitude at DUNE's near and far detectors, except for a few parameters which remain weaker at the far detector.